2008
DOI: 10.1128/aem.01199-07
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the lux Operon of Natural Dark Mutants in the Genus Vibrio

Abstract: Bacterial bioluminescence can display a wide range of intensities among strains, from very bright to undetectable, and it has been shown previously that there are nonluminous vibrios that possess lux genes. In this paper, we report the isolation and characterization of completely dark natural mutants in the genus Vibrio. Screening of over 600 Vibrio isolates with a luxA gene probe revealed that approximately 5% carried the luxA gene. Bioluminescence assays of the luxA-positive isolates, followed by repetitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Bioluminescence is a trait scattered throughout the family Vibrionaceae; however, the selective pressures driving the evolution of bioluminescence are not always clear (62). As noted here, the mystery deepens in that light output can vary by over several orders of magnitude between different environmental isolates of V. fischeri, and this is true for other Vibrio species as well (23,49). The work here provides evidence that lux has evolved relatively rapidly in V. fischeri and helps provide a foundation for understanding the mechanistic differences leading to dimmer or brighter strains.…”
Section: Vol 77 2011 Evolution Of Lux and Brightness In V Fischerimentioning
confidence: 78%
See 1 more Smart Citation
“…Bioluminescence is a trait scattered throughout the family Vibrionaceae; however, the selective pressures driving the evolution of bioluminescence are not always clear (62). As noted here, the mystery deepens in that light output can vary by over several orders of magnitude between different environmental isolates of V. fischeri, and this is true for other Vibrio species as well (23,49). The work here provides evidence that lux has evolved relatively rapidly in V. fischeri and helps provide a foundation for understanding the mechanistic differences leading to dimmer or brighter strains.…”
Section: Vol 77 2011 Evolution Of Lux and Brightness In V Fischerimentioning
confidence: 78%
“…For example, obvious visible luminescence has been frequently associated with a number of species, such as Vibrio fischeri, Vibrio harveyi, Photobacterium leiognathi, and Photobacterium phosphoreum; however, dim and even "cryptic" luminescence has also been observed upon careful examination of certain isolates, such as Vibrio salmonicida (20). Even isolates of the same species can vary in luminescence output (23,49). Such variation is dramatically evident in V. fischeri (5,32,45,62), which is a longstanding model for studying bioluminescence, its functional roles, and its regulation.…”
mentioning
confidence: 99%
“…The work suggests that broader, relatively unbiased environmental samplings may increase the general knowledge of the bioluminescence spectrum for any given species of Vibrionaceae . Samplings of both Vibrio cholerae and V. harveyi support this conclusion; such studies have demonstrated that non‐bioluminescent isolates of luminous species are as abundant, or more abundant, than bioluminescent isolates in marine environments (Grim et al ., 2008; O'Grady and Wimpee, 2008; Zo et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). These results have ecological significance, as nonluminescent luxR defectors and UC luxO mutants have all been identified in natural Vibrio populations (43)(44)(45). Importantly, this occurred in a well-mixed environment in which no biofilms or cell aggregates were observed and neither assortment of competitors nor privatization of PG would be likely.…”
Section: Discussionmentioning
confidence: 99%